Solid Pseudopapillary Tumor of the Pancreas with Concomitant Pancreas Divisum. A Case Report - Watanabe, Daisuke; Miura, Kouichi; Goto, Takashi; Nanjo, Hiroshi; Yamamoto, Yuzo; Ohnishi, Hirohide (JOP. Journal of the Pancreas, 2016)
Context Solid pseudopapillary tumor of the pancreas is a rare neoplasm which affects young women. On the other hand, pancreas divisum is an anomaly which develops at 7 weeks of gestation. Here, we report a case of a solid pseudopapillary tumor of the pancreas with concomitant pancreas divisum. Case report A 26-year-old woman was diagnosed as having a pancreatic tumor with solid and cystic components in the pancreatic head. Pancreatograms obtained by ERCP and MRCP showed no communication between the ventral and dorsal pancreatic ducts, indicating that pancreas divisum was present. Microscopically, the resected tumor had solid and cystic components. Immunohistochemical study demonstrated that the tumor cells were positive for alpha-1-antitrypsine, vimentin and progesterone receptor but negative for estrogen receptors, NSE, insulin or glucagon. The tumor was diagnosed as a solid pseudopapillary tumor of the pancreas. Although more than 700 cases of solid pseudopapillary tumors of the pancreas have been reported in the English literature, a search of PubMed turned up no reports of concomitant solid pseudopapillary tumor and pancreas divisum. Conclusion Solid pseudopapillary tumors of the pancreas with concomitant pancreas divisum are extremely rare. Image: Well-circumscribed solid mass with hemorrhagic degeneration.